Are in‐office breathing exercises effective for adults presenting to primary care with anxiety or panic disorders?. Issue 6 (June 2018) - Seferovic, Admir; Kirmse, Raquel; Harris, Geri; Alford, Ursula; Dalgleish, Dana; Rice, Tina; Rivera, Floribeth; Paul, David; Wortz, Kathryn
Abstract : EVIDENCE‐BASED ANSWER : Perhaps. Breathing exercises assisted by capnography have similar efficacy for anxiety and panic symptoms as cognitive restructuring techniques and, as a standalone treatment, are generally associated with better symptom relief than control interventions (SOR: C, single small RCT and systematic review of small observational studies). Furthermore, breathing exercises, as a component of cognitive behavioral therapy (CBT) and medication management by trained clinicians, improve anxiety symptoms more than usual care (SOR: B, RCT).